If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-31+7k=6(k-6)
We move all terms to the left:
-31+7k-(6(k-6))=0
We calculate terms in parentheses: -(6(k-6)), so:We get rid of parentheses
6(k-6)
We multiply parentheses
6k-36
Back to the equation:
-(6k-36)
7k-6k+36-31=0
We add all the numbers together, and all the variables
k+5=0
We move all terms containing k to the left, all other terms to the right
k=-5
| 8x-6x-20=10 | | 4x/20=x-3/2 | | 15r-18=14r-10 | | 47=2v+11 | | s÷4=6 | | x+18.01=2.68 | | 2/3y+8=26 | | -11p+13=-2p-17p-19 | | |3m|=12 | | 6j+8=2j-16 | | 20-5u+20=7u-20 | | -6/7=k(-18/35) | | 6=3m+14 | | 777=x+469 | | -20+17d=14+19d | | 3-6f+19f=-8+12f | | -2p-8(-7p-4)=-p+32 | | 2z-7=5z-4 | | 2.5(x+2+4.5+1.5(x-3)=15 | | 8+7+5+6+4+n+3+7=50 | | 4w+1=4w | | 12-2(x+5)=32+3x | | 5-7k=-2k-7k-7 | | 4x=6(5-x) | | 1/3(x-3)=3x-2(x-1)+13/3 | | 8v–10=9+1+10 | | 9(z+1)^2+12=16 | | 3.5(x+3)=28 | | -w+8=-8w-6 | | -756=27x | | (625/256)^5x-4=1 | | -21=3+4u |